Scientific Information Analysis Using Text Analysis Tool “Voyant Tools” - Kairaitytė-Užupė, Aušra; Ramanauskaitė, Egidija; Rudžionis, Vytautas Evaldas (Information & Media, 2023)
This article describes the use of “Voyant Tools”, an open access text analysis application, to examine a corpus of articles from open access journals, dealing with the topic of digital humanities. The corpus consisted of 404 articles recorded in the “Clarivate Analytics Web of Science” and “Scopus ScienceDirect” databases. The authors discuss how “Voyant Tools” aids to identify the dominant fields of research through quantitative methods and to reveal the main discourse themes using distant reading and interactive reading capabilities. They also identify some problems encountered during the analyses, and also discuss the usefulness of data visualization for research and interpretation. Computer tools can be useful for experienced researchers who are interested in quantitative text analysis, as well as for beginners, as it provides an opportunity to acquire basic knowledge that will lead to a deeper interest in textual analysis methods.